Evaluasi Program Pengelolaan Hipertensi di Puskesmas Ujong Rimba Kabupaten Pidie Provinsi Aceh - Marhamah Marhamah; Farrah Fahdienie; Dharina Baharuddin (SEHATI: Jurnal Kesehatan, 2025)
Hypertension is one of the non-communicable diseases that is the main cause of cardiovascular complications in Indonesia. The prevalence of hypertension in Pidie Regency, especially the working area of the Ujong Rimba Health Center, reached 30% in 2023. Evaluation of the effectiveness of the hypertension management program is important to optimize the interventions that have been implemented. The purpose of this paper is to evaluate the implementation of the hypertension management program from the aspects of input, process, output, outcome, and impact at the Ujong Rimba Health Center, Pidie Regency, Aceh Province. The method used in the study used an evaluative method with a mixed approach (mix method). Subjects consisted of hypertensive patients registered in 2022–2024. Data were collected through questionnaires, in-depth interviews, observations, and document reviews, then analyzed descriptively and qualitatively. The results of this program showed positive achievements in increasing service coverage (87% in 2024), therapy compliance (up from 35% to 87%), and decreasing blood pressure (75% of patients showed improvement). However, there are obstacles in terms of human resources, budget, drug availability, and implementation of SOPs. The hypertension management program is running quite effectively, but needs improvement in terms of resources and program governance.